Knowledge mapping of micro/nanomotors in cancer treatment: a bibliometric analysis (2006–2025) - Ying Song; Kai Zhao; Yan Yang; Haiming Yu (Discover Oncology)
Abstract Background Malignant tumors present challenges such as high heterogeneity and the limitations of traditional therapies, driving innovations in nanomedicine, particularly in the development of micro/nanomotors. These autonomous devices offer superior tumor penetration capabilities but and lack systematic bibliometric insights. Method Data from WoSCC (2006–2025) were analyzed using bibliometric tools (CiteSpace, VOSviewer, and “bibliometrics”) to map research landscapes. Results A total of 10,609 articles from 38 countries were identified, with annual output growing at a compound annual growth rate (CAGR) of 22% and peaking at 126 articles in 2024. China led globally with 380 publications (62.4%). The Chinese Academy of Sciences (123 articles) emerged as the leading institution in this domain, while ACS NANO (36 articles) was identified as the most prolific and co-cited journal. Wang J contributed the highest number of articles, and publications by Wang J also exhibited the highest co-citation frequency. The keyword “penetration” exhibited the strongest citation burst (2021–2025), reflecting breakthroughs in overcoming tumor physical barriers. Conclusion This study highlights China’s dominance, rapid technological evolution toward intelligent actuation and immunotherapy integration, and “penetration” as a pivotal frontier. Findings provide strategic guidance for future research and clinical translation.